Is populism reversible? Evidence from Italian local elections during the pandemic - Massimo Bordignon; Federico Franzoni; Matteo Gamalerio (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2023)
We study the effect of economic insecurity on electoral outcomes using data on municipal elections in Italy. We implement a difference-in-differences approach that exploits exogenous variation across municipalities in the share of inactive workers due to the economic lockdown introduced by the central government to deal with the Covid-19 pandemic. We show that lockdown-induced economic insecurity positively affected the electoral performance of progressive and left-wing parties, while it negatively affected conservative and far-right parties. Conversely, we find no effect for the populist Five Star Movement, local independent parties (i.e., Civic Lists), and electoral turnout. We provide evidence that extraordinary economic measures introduced by the central government to compensate workers for the economic insecurity can explain this shift in partisanship toward the left and the increasing support for pro-EU parties, away from euro-skeptic and populist forces.
Keywords: D70; D72; D91; 330; COVID-19; Elections; Voting behaviour; Populism; Economic Insecurity